Canadian Children's Physical Activity and Sedentary Behaviors During Time-Segments of the School Day. Issue 4 (4th July 2022) - da Costa, Bruno Gonçalves Galdino; Bruner, Brenda; Scharoun Benson, Sara; Raymer, Graydon; Law, Barbi
ABSTRACT: Background: Schools play an important role in promoting physical activity (PA) through school day schedules and policies. Purpose: To investigate different intensities of children's movement behavior during instructional time, recess, and in relation to the Ontario Daily Physical Activity (DPA) policy. Methods: Movement behavior intensities were assessed using accelerometers during 5 school days. Behaviors were calculated for learning blocks, recesses, and physical education classes. Participants with ≥20 min of moderate-vigorous physical activity (MVPA)/day were considered compliant with the DPA policy. Results: The sample included 159 children (52% female, 9.03 ± 1.66 years old). In all school day segments, sedentary behavior was higher than light PA and MVPA combined, and 21% met the DPA requirement. Females spent more time sedentary and less time in light PA and MVPA than males in all school day segments. Age was inversely associated with light PA and positively related to sedentary behavior. Participants who met the DPA requirement spent less time in sedentary behavior and more time in light PA and MVPA during school segments. Discussion: Most of the time spent at school is sedentary behavior. There is room to potentialize the promotion of physical activity in physical and health education classes and enhance DPA. Translation to Health Education Practice: Our findings suggest that there is a need to strengthen DPA and improve the physical activity levels of children in school.